Ofranergene obadenovec (VB-111) in platinum-resistant ovarian cancer; favorable response rates in a phase I/II study are associated with an immunotherapeutic effect - Arend, Rebecca C.; Beer, Hannah M.; Cohen, Yael C.; Berlin, Suzanne; Birrer, Michael J.; Campos, Susana M.; Rachmilewitz Minei, Tamar; Harats, Dror; Wall, Jaclyn A.; Foxall, McKenzie E.; Penson, Richard T. (Gynecologic oncology, 2020)
Report final results of a phase I/II study of VB-111, a targeted anti-cancer gene therapy with a dual mechanism: anti angiogenic/vascular disruption and induction of an anti-tumor directed immune response, in combination with paclitaxel in patients with platinum-resistant ovarian cancer. Study NCT01711970 was a prospective, open label, dose escalation study assessing combination treatment of VB-111 and weekly paclitaxel. In the Phase I part of the study, patients were treated with escalating doses of intravenous VB-111 and paclitaxel. In Phase 2, patients were treated with therapeutic doses of VB-111 and paclitaxel 80 mg/m2. Assessments included safety, overall survival (OS), progression free survival (PFS), and tumor response (CA-125 and RECIST). 21 patients with recurrent platinum-resistant ovarian cancer were enrolled. 17/21 received the therapeutic dose. Patients had a median of 3 prior lines of therapy. Half of the subjects were platinum refractory, and half were previously treated with antiangiogenics. No DLTs were observed. VB-111 was well tolerated and associated with mild flu-like symptoms. In the therapeutic dose cohort, a 58% CA-125 GCIG response rate was seen in evaluable patients. The median OS was 16.6 months in patients treated with therapeutic dose compared to 5.8 months in sub-therapeutic dose (p = 0.028). Tumor specimens taken after treatment demonstrated tumor infiltrated with cytotoxic CD8 T-cells in regions of apoptotic cancer cells. Treatment with VB-111 in combination with paclitaxel was safe and well tolerated. Favorable tumor responses and overall survival outcomes were associated with induction of an immunotherapeutic effect. •VB-111 has a dual mechanism targeting tumor vasculature and inducing anti-tumor immune effects turning “cold” tumors “hot”.•VB-111 with paclitaxel had a 58% CA-125 response rate that correlated with a survival benefit.•VB-111 in combination with paclitaxel had a similar OS effect and better CA-125 response than in the AURELIA study.•VB-111 was safe and well tolerated.